New record of Yosiiella mira Hüther, 1967 (Collembola, Isotomidae, Anurophorinae) for Amazon - Cipola, Nikolas G.; Villalobos, Erick A. H. (Entomological Communications, 2022)
Yosiiella mira Hüther, 1967 is recorded here for the first time outside Brazilian territory, in Peruvian Amazon. The species was found through of litter extraction from an ore exploration area. From this record, we believe that Y. mira could potentially be widely distributed in the Amazon biome. The Isotomidae fauna from Peru now pass for 34 species in 14 genera.